Flight Dynamics Modeling and Dynamic Stability Analysis of Tilt-Rotor Aircraft - Ke Lu; Chunsheng Liu; Chunhua Li; Renliang Chen (International Journal of Aerospace Engineering)
The tilt-rotor aircraft has often been proposed as a means to increase the maximum speed of the conventional helicopter. The tilt-rotor aircraft consists of three primary flight modes that are the helicopter flight mode in low forward speed flight, airplane flight mode in high forward speed flight, and conversion flight mode. The aim of this paper is to develop a nonlinear flight dynamics mathematical modeling method of tilt-rotor aircraft and investigate the dynamic stability characteristics of tilt-rotor aircraft. First, a nonlinear tilt-rotor aircraft flight dynamics model is developed. The trim and linearized results are present to verify the model. Then, using a numerical differentiation technique, the dynamic stability of the tilt-rotor aircraft is assessed. The results show that the flight speed and nacelle angle would affect the magnitude and the trend of the aerodynamic derivatives. The damping of the pitch short period mode and the Dutch roll mode is insensitive to flight speed while they could be affected by nacelle angle. In all flight modes, as flight speed increases, the natural modes become more stable.